A importância das práticas pedagógicas no ensino de proteínas: uma reflexão das teorias de aprendizagem e possibilidades metodológicas - Cancian, Maria Yasmin (Universidade Federal de São Carlos, 2024)
This work consists of a reflection based on the review of pedagogical proposals in teaching proteins in the high school biology discipline and how the learning theories described by the authors, Ausubel, Chevallard and Piaget, occur. Through the use of these practices, we seek to make the abstract concepts of biology real, finding ways to facilitate learning about the functions and synthesis of proteins, seen as content that is poorly contextualized according to the experience during the biology internship. The research used the Google Scholar platforms, the Scientific Electronic Library Online (SCIELO) and Education Resources Information Center (ERIC) regarding pedagogical proposals and with the help of searching for the descriptors “protein teaching”; “protein pedagogical practices”, obtaining 48 scientific articles in the period from 2006 to 2021. The methodologies used in the articles analyzed were grouped as forms of games, use of software, textual analysis, and case-based learning. The research revealed that sometimes the tools are varied, but there are more recurrent methodologies and different proposals that are less common, these can be efficient tools in teaching proteins. Therefore, there are increasing attempts to make this content more contextualized and understandable. A didactic sequence is created that can be used to explain the topic, entitled “the house of proteins”.
The importance of pedagogical practices in protein teaching: a reflection on learning theories and methodological possibilities
Keywords: Biologia; Ensino; Proteínas; Práticas Pedagógicas; Metodologia; Biology; Teaching; Proteins; Pedagogical practices; Methodology; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO